Effect of plant extracts on H2O2-induced inflammatory gene expression in macrophages - Pomari E (Dove Medical Press, 2014)
Elena Pomari, Bruno Stefanon, Monica Colitti Department of Agricultural and Environmental Sciences, University of Udine, Udine, Italy Background: Arctium lappa (AL), Camellia sinensis (CS), Echinacea angustifolia, Eleutherococcus senticosus, Panax ginseng (PG), and Vaccinium myrtillus (VM) are plants traditionally used in many herbal formulations for the treatment of various conditions. Although they are well known and already studied for their anti-inflammatory properties, their effects on H2O2-stimulated macrophages are a novel area of study. Materials and methods: Cell viability was tested after treatment with increasing doses of H2O2 and/or plant extracts at different times of incubation to identify the optimal experimental conditions. The messenger (m)RNA expression of TNFα, COX2, IL1β, NFκB1, NFκB2, NOS2, NFE2L2, and PPARγ was analyzed in macrophages under H2O2 stimulation. The same genes were also quantified after plant extract treatment on cells pre-stimulated with H2O2. Results: A noncytotoxic dose (200 µM) of H2O2 induced active mRNA expression of COX2, IL1β, NFE2L2, NFκB1, NFκB2, NOS2, and TNFα, while PPARγ was depressed. The expression of all genes tested was significantly (P<0.001) regulated by plant extracts after pre-stimulation with H2O2. COX2 was downregulated by AL, PG, and VM. All extracts depressed IL1β expression, but upregulated NFE2L2. NFκB1, NFκB2, and TNFα were downregulated by AL, CS, PG, and VM. NOS2 was inhibited by CS, PG, and VM. PPARγ was decreased only after treatment with E. angustifolia and E. senticosus. Conclusion: The results of the present study indicate that the stimulation of H2O2 on RAW267.4 cells induced the transcription of proinflammatory mediators, showing that this could be an applicable system by which to activate macrophages. Plant extracts from AL, CS, PG, and VM possess in vitro anti-inflammatory activity on H2O2-stimulated macrophages by modulating key inflammation mediators. Further in vitro and in vivo investigation into molecular mechanisms modulated by herbal extracts should be undertaken to shed light on the development of novel modulating therapeutic strategies. Keywords: inflammation, qRT-PCR, RAW264.7 cells, nutraceuticals